Fungicide resistance profiles of Alternaria spp. associated with fruit rot of blueberry in Georgia, USA - Beg, Mirza Ashikul; Aktaruzzaman, Md.; Lewis, Kippy J.; Oliver, Jonathan E. (Frontiers in Plant Science, 2025)
Georgia blueberry growers experience significant losses annually due to fruit rots including Alternaria rot caused by Alternaria spp. Fungicide applications from bloom through harvest are typically recommended for management of fruit rots, however fungicide resistance development has the potential to complicate management activities by reducing fungicide efficacy. To evaluate fungicide resistance issues in Georgia, 46 isolates of Alternaria spp. from ripe blueberry fruit from four major blueberry-producing counties were collected and identified by morphological and molecular features. The majority of the isolates were Alternaria alternata (n=43) but also included Alternaria tenuissima (n=1), Alternaria dumosa (n=1), and Alternaria limoniasperae (n=1). All isolates were assessed for resistance to fungicides which included fludioxonil, fluazinam, metconazole, cyprodinil, pydiflumetofen, boscalid, and pyraclostrobin. For all tested fungicides, with the exception of pyraclostrobin, a mycelial growth inhibition assay was used to determine the EC50 values. For pyraclostrobin, a spore germination assay was used. EC50 value ranges of A. alternata for fludioxonil, fluazinam, cyprodinil, metconazole, pydiflumetofen, boscalid, and pyraclostrobin were 0.037 to 0.234 µg/mL, 0.025 to 0.125 µg/mL, 0.015 to 0.404 µg/mL, 0.125 to 5.729 µg/mL, 0.008 to 1.114 µg/mL, 0.551 to >100 µg/mL, and 0.04 to >100 µg/mL, respectively. These EC50 values suggest that all tested Alternaria spp. isolates were sensitive to fludioxonil, fluazinam, metconazole, and cyprodinil. However, 12 Alternaria spp. isolates showed reduced sensitivity to pydiflumetofen, 21 were resistant to boscalid and 10 were resistant to pyraclostrobin. Among these resistant isolates, 6 were resistant to both of the two latter fungicides. Sequencing portions of the sdhB, sdhC and sdhD genes from boscalid-resistant isolates and the cytochrome b gene from pyraclostrobin-resistant isolates revealed the presence of known resistance mutations in resistant isolates - including H134Q or G79R mutations in the sdhC gene or H134R mutations in the sdhD gene of some, but not all, boscalid-resistant isolates, and the presence of the G143A mutation in pyraclostrobin-resistant isolates. Our findings indicate that resistance to boscalid and pyraclostrobin is present in Alternaria spp. from Georgia blueberries and suggest that growers utilizing these fungicides in some Georgia locations may experience Alternaria fruit rot control failures.